Mediating effect of ethnocentrism on relationship between social networking site factors and social solidarity - Ridzuan, Abdul Rauf (2016)
This study is done in order to find ways on how social networking sites (SNS) can unite multiethnic people in Malaysia as the level of community tension index has been increasing since 2011 until now. Social networking sites is chosen as it brings many benefits to the users. This study also aims to examine the relationship between SNS factors (interaction, involvement, quality and intimacy) towards ethnocentrism and social solidarity. To address the research questions, a literature review of antecedents toward ethnocentrism and social solidarity were conducted. The literature review emphasized five principles in social solidarity namely equality, willingness, sharing, recognition and duties and also four elements of ethnocentrism namely stereotype, mistrust, avoidance and differential treatment. This study used social capital and social solidarity theory as foundations theories for model development. The minimum sample size was determined through Krejcie and Morgan table. The study involved 482 respondents, selected through a purposive sampling technique involving three main ethnics in Malaysia. A cross sectional survey and structured questionnaire were used for data collection. A quantitative survey was designed using self-administrated questionnaire. All variables were measured through scales previously used by other researchers. The scales were checked for convergent and discriminant validity using Confirmatory Factor Analysis (CFA). Structural Equation Modeling (SEM) under AMOS software was used in the analysis. Results of the SEM indicated that the model fits the data. The findings indicated that two SNS factors namely interaction and intimacy have significantly influence social solidarity. Moreover, the result showed that two SNS factors which are interaction and involvement also have significance influence on ethnocentrism. Result from the study also found that the mediating variable which is ethnocentrism has a positive effect on the relationship between involvement and social solidarity. The results of this study showed 61.3% of variance of social solidarity was explained by the proposed model. In addition, this study contributes knowledge on SNS factors, ethnocentrism and social solidarity.